INITIATION OF INTENSIVE NATIVE CHICKEN RAISING PATTERNS, THROUGH CONSTRUCTION OF COLONY CAGES ON WOMEN'S FARMER GROUP'S YARD - Hardyta, Galy; Haris Septian, Mohamad; Siswanto, Usman; Dewi Setyowening, Natalia; Elisa, Elisa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Native chickens have a good potential for production and business opportunities in intensive rearing. Rural communities that have raised native chickens traditionally have difficulties in implementing the intensive rearing method directly. Changes in society can be achieved through a program of activities resulting from social planning which is implemented in stages, systematically, and sustainably. This Community Service Program was aimed to assist rural communities in adopting the intensive rearing method of native chickens gradually. This program was focused on counseling about the management of domestic chicken rearing and the application of the Cage management system by changing the rearing of native chickens from umbaran to colony cage system on the land owned by the Kelompok Wanita Tani (KWT). Counseling was able to provide additional insight and basic knowledge regarding the intensive rearing of native chickens. The colony cages construction on KWT land was the initial stage of adopting an intensive rearing system. Through this program, KWT members also discovered several problems, which can be solved by this program or by the further implementation of this community service program.